A VHDL Implemetation of the Advanced Encryption Standard - Loban, H. (NURE, MC&FPGA, 2019)
A new original approach to realization of AES algorithm on FPGA is proposed. Problems of VHDL modeling of AES ciphering and deciphering are considered.
Keywords: AES; triple DES; encryption; decryption; FPGA; VHDL